Didactic Requirements of the Civil Defense Course Given in the Career of Medicine at the University of Ciego De Avila - Martínez-Díaz, Yeniska (2017)
The article approaches the characteristics of the Civil Defense course given at the University of Medical Sciences of Ciego de Avila, set for the education of future doctors to face disasters and contingency situations. In previous studies, it was detected that students of medicine are not prepared to face tasks related to this when practicing their profession; that is why the objective of this article is to share with the scientific community the didactic requirements that must be assumed in the teaching-learning process of those who practice medicine, and in the educational development preparing them to face disasters and act accordingly in contingency situations from their own professional functions. The requirements aim to conceive the teaching-learning process in interrelation with the history of the medical profession; this implies a coherent and a creative way of developing historical elements and establishing empathic and interdisciplinary links with the study of the functions of today’s medicine, in which the role of academic, labor, and research components are enhanced. The research methodology implemented was the experimental approach in its variant of pedagogical pre-experiment, with pretest and posttest designs, with a group of students of the career of Medicine. These students took part in surveys and interviews and were observed during the teaching-learning process in order to elaborate the diagnosis. Documents were reviewed and contrasted with the didactic theory; the teaching-learning process was modeled with the new didactic requirements; finally, a pedagogical experiment was carried out, and it let improving the design of the Civil Defense course for the Medicine career. The posttest results show significant changes in the teaching-learning process, which confirmed the idea that the more participative and contextual is the process, the more effective is the education and the greater is the preparation the future doctors acquire to face disasters and contingency situations from their professional functions.